Intervening Health Behavior in Health Communication Literacy on Public Health in the 2020-2021 Pandemic - K. Y.S. Putri; Neneng Siti Silfi Ambarwati; Andy Hadiyanto; S Bekti Istiyanto; Rayni Delya Hafni (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
There is a lot of information on health and pandemics that almost makes people's behavior change. Healthy people's behavior has become a habit. The formulation of the research problem is whether there is an effect of health communication literacy on public health mediated by the healthy behavior of the community. The research objective was to see the effect of health communication literacy on public health mediated by the healthy behavior of the community. Many previous studies have supported this research. The concepts used in this research are health communication literacy, healthy behavior, and public health. The research method used is quantitative explanative. With questionnaires and interviews with various health policymakers, health observers, patients who have recovered from Covid-19, and people who have not been exposed to Covid-19. The validity and reliability of this study are positive so we can look to the next step. The descriptive results of this study point to the positive direction of the three variables. This means that all variables are manifested positively by the respondent on the statements made by the researcher. In the next statistical test using simple regression that the effect of health communication literacy on public health has a strong effect by using the intervention variable, namely health behavior. Interviews with informants stated that social media was used by the public on visits to health pages in a pandemic. And public health behavior greatly changes people's lives and has a strong effect on public health. Suggestions in this study that health communication literacy can affect public health with public health behavior during a pandemic. Keywords: Health Communication Literacy, Health Communication, Health